The Wonderful Gold Treasures of Marlik: A First Report from a Newly Discovered 1st Millennium B. C. Mound in Northern Iran - Negahban, Ezat O.
cf. “Further Finds from Marlik” ILN May 5, 1962, 699- 701, 23 fig.